2018
DOI: 10.1038/s41598-018-28138-x
|View full text |Cite
|
Sign up to set email alerts
|

Novel haptens and monoclonal antibodies with subnanomolar affinity for a classical analytical target, ochratoxin A

Abstract: Ochratoxin A is a potent toxic fungal metabolite whose undesirable presence in food commodities constitutes a problem of public health, so it is strictly regulated and controlled. For the first time, two derivatives of ochratoxin A (OTAb and OTAd) functionalized through positions other than the native carboxyl group of the mycotoxin, have been synthesized in order to better mimic, during the immunization process, the steric and conformational properties of the target analyte. Additionally, two conventional hap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Recent experimental studies have revealed the importance of the native carboxylic group in the OTA natural conformation in biological systems . This carboxylic group can strongly contribute to the binding of monomers during MIP synthesis, and we have proven previously the importance of this group for producing antibodies . In this research, we explore the possibility of mimicking protein‐based receptors using nanoMIPs and reaffirm the importance of OTA natural functionalities in “immunogenic” properties of this template.…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…Recent experimental studies have revealed the importance of the native carboxylic group in the OTA natural conformation in biological systems . This carboxylic group can strongly contribute to the binding of monomers during MIP synthesis, and we have proven previously the importance of this group for producing antibodies . In this research, we explore the possibility of mimicking protein‐based receptors using nanoMIPs and reaffirm the importance of OTA natural functionalities in “immunogenic” properties of this template.…”
Section: Introductionmentioning
confidence: 68%
“…[13] This carboxylic group can strongly contribute to the binding of monomers during MIP synthesis, and we have proven previously the importance of this group for producing antibodies. [14] In this research, we explore the possibility of mimicking protein-based receptors using nanoMIPs and reaffirm the importance of OTA natural functionalities in "immunogenic" properties of this template. To this purpose, we have prepared nanoMIPs by solid phase synthesis using the haptens OTAb and OTAe (Figure 1), two carboxylated derivatives of OTA previously reported for the production of antibodies.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations